THE THE EFFECT OF EMOTIONAL INTELLIGENCE AND SELF-EFFICACY ON THE ETHICAL JUDGMENT OF FUTURE ACCOUNTANTS IN EASTERN INDONESIA - Putuhena, Hempry; Marlyn Paru, Sara; Josefien Viotty Radianto, Amelia (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2025)
Ethical decision making is a very crucial decision by an accountant. Ethical decisions have a moral content that must be upheld by accountants. The purpose of this study is to investigate the impact of emotional intelligence and self-efficacy on the ethical judgment of future accountants in Eastern Indonesia. The focus of eastern Indonesia refers to the potential for the region to develop in the future. This study uses a quantitative approach with data management using SPSS. 116 respondent data were processed using SPSS and showed that emotional intelligence had no effect on ethical judgment while self-efficacy had a negative effect on the ethical judgment of future accountants in eastern Indonesia. The limitation of this study is that the respondents came from 2 universities in eastern Indonesia, so that in the future, in order to enrich the results of similar studies, further researchers can use many respondents in different locations